Association between social determinants of health and rates of liver transplantation in individuals with cirrhosis. Issue 4 (8th April 2022) - Flemming, Jennifer A.; Muaddi, Hala; Djerboua, Maja; Neves, Paula; Sapisochin, Gonzalo; Selzner, Nazia
Abstract: Background and Aims: This study evaluated the association between neighborhood‐level social determinants of health (SDOH) and liver transplantation (LT) among patients with cirrhosis who have universal access to health care. Approach and Results: This was a retrospective population‐based cohort study from 2000–2019 using administrative health care data from Ontario, Canada. Adults aged 18–70 years with newly decompensated cirrhosis and/or HCC were identified using validated coding. The associations between five neighborhood level SDOH quintiles and LT were assessed with multivariate Fine‐Gray competing risks regression to generate subdistribution HRs (sHRs) where death competes with LT. Overall, n  = 38, 719 individuals formed the cohort (median age 57 years, 67% male), and n  = 2788 (7%) received LT after a median of 23 months (interquartile range 3–68). Due to an interaction, results were stratified by sex. After multivariable regression and comparing those in the lowest versus highest quintiles, individuals living in the most materially resource‐deprived areas (female sHR, 0.61; 95% CI, 0.49–0.76; male sHR, 0.55; 95% CI, 0.48–0.64), most residentially unstable neighborhoods (female sHR, 0.61; 95% CI, 0.49–0.75; male sHR, 0.56; 95% CI, 0.49–0.65), and lowest‐income neighborhoods (female sHR, 0.57; 95% CI, 0.46–0.7; male sHR, 0.58; 95% CI, 0.50–0.67) had ~40% reduced subhazard for LT ( p  < 0.01 for all). No associations were found between neighborhoods with the most diverse immigrant or racial minority populations or age and labor force quintiles and LT. Conclusions: This information highlights an urgent need to evaluate how SDOH influence rates of LT, with the overarching goal to develop strategies to overcome inequalities. Abstract : The graphical abstracts shows association between social determinant of health and rates of liver transplantation in patients with liver cirrhosis.